Suicide Stigma in Christian Faith Communities: A Qualitative Study - Mason, Karen (Religions, 2021)
Given the increasing numbers of U.S. lives lost to suicide, it is imperative to identify factors that can help protect against suicide. While regular religious service attendance has been found to be protective against suicide, faith communities have taboos against suicide which may be associated with stigma. Nine Christian faith leaders and congregants and one moral psychologist completed interviews on suicide stigma in Christian faith communities. Themes that emerged included internal, interpersonal, and theological components and group differences related to suicide stigma in Christian faith communities. Participants proposed seven barriers and seven corresponding ways to address suicide stigma in Christian faith communities: talk about suicide, address skill deficits, practice vulnerability, get leadership on board, address the theology of suicide, appreciate that faith communities have a unique contribution to make to suicide prevention, and address cultural/systemic issues.